THE ADDITION OF COCONUT WATER THROUGH FEED EFFECTIVE ON MASCULINIZATION OF GUPPY FISH (Poecilia reticulata) - Sektiana, Sinar Pagi; Zulendra, Muhammad Fiqi; Rina, Rina; Rahardjo, Sinung (Indonesian Aquaculture Journal, 2024)
The production of male guppies is more desirable due to it higher selling value than females. One way to produce male guppies is change it sex, namely masculinization which can be enhanced through the addition of coconut water, with high potassium level. Potassium can convert all cholesterol in the larvae into pregnenolone, which functions to convert estrogen into progesterone and produces testosterone. Hormones required in sex change can be supplemented by the oral method through feed. The research, which was conducted from November 2022 - March 2023, was divided into two stages, first is to determine the dosage of coconut water and the second one is to determine the appropriate coconut water sterilization method. Each stage used a completely randomized design with four treatments and four replicates. Doses of coconut water added to feed were 0.06 ml/g feed, 0.09 ml/g feed, 0.12 ml/g feed, and 0.15 ml/g feed. The sterilization methods conduct in this research are using UV light, autoclave, and ozone. Observation of male genitalia was done after 45 days by observing the urogenital organs and confirmed by hematoxylin-eosin histological staining after 52 and 59 days. The highest percentage of male guppies at 71.75% was produced by the dose of 0.15 ml/g feed, while sterilization treatment produces lower male percentage than control (p<0.05).  No significant difference in fish survival was obtained. Fish survival ranges from 88% - 93%. Thus, the addition of 0.15 ml of coconut water to feed is the most effective treatment in producing male guppies.